Dual-stage Er/Yb doped fiber amplifier for gain and noise figure enhancements - Harun, Sulaiman Wadi; Abdul Rashid, Hairul Azhar; Muhd-Yassin, S. Z.; Abd-Rahman, M. K.; Tamjis, M. R.; Ahmad, Harith (The Institute of Electronics, Information and Communication Engineers, 2006)
Gain and noise figure enhancements in an Er/Yb doped fiber amplifier (EYDFA) are demonstrated using a dual-stage amplifier configuration. In comparison to a conventional single-stage amplifier, the gain in this amplifier is enhanced at all wavelengths between 1530 to 1560 nm for the input signal powers of - 40 and 0 dBm. A maximum gain improvement of 7.3 dB is obtained at a small signal (- 40 dBm) wavelength of 1534 nm. The noise figure of the design is also enhanced at all wavelengths between 1530 to 1560 nm with a maximum reduction of 3.0 dB obtained at the small signal wavelength (- 40 dBm) of 1542 nm. The total pump power used in this design is fixed at 140 mW. This improvement of gain and noise characteristics is attributed to the efficient pump power distribution within the amplifier and also the addition of a midway optical isolator between the two amplifier stages. The isolator blocks the backward propagating ASE to increase the population inversion at the first stage and thus, enhances the amplifier gain and noise figure. These results show that the usage of a dual-stage configuration with a midway optical isolator is an invaluable consideration when constructing a practical EYDFA.